Dextrose concentration for prolotherapy: A study on human neuroblastoma cells - Özlem Karasimav; Zehra Dilşad Çoban (Gülhane Tıp Dergisi, 2023)

(untitled)
Aims:Prolotherapy is performed using a 15%-concentrated hypertonic dextrose solution that targets damaged soft tissues to induce a regenerative process. A novel technique pointing at perineural regions using 5%-concentrated dextrose is also gaining popularity in daily clinical practice. Animal and human studies have revealed the clinical and functional benefits of perineural prolotherapy; however, the cytological effects of dextrose solution are immature. This study compared the effects of dextrose solutions at different concentrations on neurons at the cytological level.Methods:Cultures of human neuroblastoma cell lines that simulate neurons at the cytological level were prepared. The sample cultures consisted of the control group (CG), 5% dextrose-supplemented group (5DG), and 15% dextrose-supplemented group (15DG). The neuronal viability assay of the cultures before and 6 h after supplementation was compared between the groups.Results:The pre-supplementation cell viability percentage of CG was presumed to be 100%. The post-supplementation cell viability percentages of CG, 5DG, and 15DG were 93.33%, 22.22%, and 0%, respectively. The decreases in cell viability in both dextrose groups were statistically significant when compared with CG (p<0.001). Moreover, the difference in cell viability between the 5DG and 15DG groups was also statistically significant (p<0.001).Conclusions:Our findings suggest that dextrose solution has an acute, concentration-dependent toxic effect on cultured human neuroblastoma cells.